IMPLEMENTASI METODE UMMI DALAM PEMBELAJARAN TAHFIDZ AL-QUR'AN DI PONDOK PESANTREN MODERN ZAM-ZAM MUHAMMADIYAH CILONGOK - Azhar Muhammad, Hanafi; Suparjo (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
This study explores the application of the Ummi method in the Tahfidz Al-Qur'an program at the Zamzam Muhammadiyah Modern Islamic Boarding School in Cilongok, focusing on three main aspects: planning, implementation, and evaluation of the method in improving students' memorization. The aim is to comprehensively describe the implementation of the Ummi method and identify supporting and inhibiting factors in the process. This study uses a qualitative descriptive approach with data collection techniques through observation, in-depth interviews, and documentation studies. Data analysis is carried out through data reduction, data presentation, and verification of conclusions. The results show that the Ummi method is implemented systematically and has a positive impact on improving student memorization and discipline. The planning includes understanding the Islamic boarding school curriculum, setting memorization targets, preparing a schedule for muroja'ah and recitation, and training teachers to ensure teaching meets Ummi standards. In addition, learning tools such as guides, assessment instruments, and periodic evaluation schemes are also prepared. The implementation includes joint muroja'ah, memorization guidance through talaqqi and tasmi', daily recitation per individual, and intensive mentoring for students who experience difficulties. Evaluation is carried out routinely by assessing the fluency of memorization, accuracy of tajwid, and discipline of students, while also analyzing obstacles and solutions implemented by teachers.